2005
DOI: 10.1007/s10384-004-0220-6
|View full text |Cite
|
Sign up to set email alerts
|

Rod and Cone a-Waves in Central Retinal Vein Occlusion

Abstract: The change in the phototransduction cascade was confirmed not only in rods but also in cones in five of our seven cases of CRVO. The ERG findings might reflect the functional change in the photoreceptor layer after the onset of CRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In an acute high intraocular pressure model of retinal ischemia, Brunette et al (1986) reported that during the rise in intraocular pressure cone function was more resilient to the effects of ischemia, but in the long term rod function recovered to higher levels, supporting our finding that rod bipolar cell function is less affected in the long term. Results from human patients with central retinal vein occlusion show variation, with some studies supporting a preferential loss in cone‐mediated function (Chen et al, 2006), and others showing no difference (Hayreh et al, 1989; Tanimoto et al, 2005). Patients with central retinal artery occlusion demonstrated a greater loss in rod‐mediated function (Machida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In an acute high intraocular pressure model of retinal ischemia, Brunette et al (1986) reported that during the rise in intraocular pressure cone function was more resilient to the effects of ischemia, but in the long term rod function recovered to higher levels, supporting our finding that rod bipolar cell function is less affected in the long term. Results from human patients with central retinal vein occlusion show variation, with some studies supporting a preferential loss in cone‐mediated function (Chen et al, 2006), and others showing no difference (Hayreh et al, 1989; Tanimoto et al, 2005). Patients with central retinal artery occlusion demonstrated a greater loss in rod‐mediated function (Machida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Such susceptibility is also supported by functional measures (the electroretinogram, ERG) from animal models of acute ischemia (Brunette, 1986;Blasco et al, 1997). However, ERG recordings from human patients with more subtle ischemia (central retinal vein occlusion) reveal no significant difference between cone versus rod mediated function (Hayreh et al, 1989;Tanimoto et al, 2005).…”
Section: Preferential Loss Of Theme Classesmentioning
confidence: 96%